Cytometry new developments - Darzynkiewicz, Zbigniew; Roederer, Mario; Tanke, H. J. (Amsterdam, Netherlands Elsevier /Academic Press, 2004)
The chapters in CYTOMETRY MCB volumes, including this 4th Edition, provide comprehensive description of particular cytometric methods and review their applications. Some chapters also describe new instrumentation and provide fundamental information on use of new fluorescent probes and on data analysis. Although the term "edition" suggests the update of earlier volumes, in fact, nearly all chapters of the 4th Edition are devoted to new topics. The authors were invited to present not only technical protocols, such as available in other methodology books that specialize in the protocol format, but also to discuss the aspects of the methodology that generally are not included in the protocols. Many chapters, thus, present the theoretical foundations of the described methods, their applicability in experimental laboratory and clinical setting, common traps and pitfalls, problems with data interpretation, comparison with alternative assays, choice of the optimal assay, etc. Some chapters review applications of cytometry and complementary methodologies to particular biological problems or clinical tasks.--Provided by publisher.
Includes bibliographical references and index.
Keywords: Flow cytometry; Cytophotometry; Cytogenetics; Electronic books